(untitled) (Global Journal of Medical Research, 2017)
Context A condition that has a stronger link to malocclusion is a forward resting posture of tongue Correction of tongue function or posture facilitates correction of the lisp or interdentalization of the t d n and l phonemes A diagnosis is needed that distinguishes learned behaviour from obligatory function due to physical deviation Inquiry into these disorders identifies subgroups characterized by different combinations of functions occlusion status speech status and forces obligating or predicting anterior tongue position Aim To correlate role of phonetics in various malocclusions evaluate the same palatographically Materials method The tongue was evenly painted with a thin mix of rubber base putty impression material the speaker was prompted to say the target word The entire pattern of contact is photographed recorded palate graphically in different type of malocclusions Conclusion When Palatography is correlated to different malocclusions the aetiology of phonetic disturbance can be incurred